Heavy Metals in the Environment - Sarkar, Bibudhendra (CRC Press, 2009)
This text presents contemporary analytical techniques for the determination of heavy metals in air particles, water, soil and biological samples. It details experimental studies to reduce the occurance of disease, remediate contaminated sites and establish acceptable range of oral intakes (AROI) guidelines.